طريقة تعليم اللغة العربية في ترقية مهارة الكلام - Nurhayati, Dewi (Lugawiyyat, 2020)
Nevertheless, lately Arabic Learning Method at both organizations deteriorated in its implementation. Therefore, it is important to be researched, to discover its problem background.This research means to compare between Arabic Learning Method for Development of Speaking Skill which was implemented at TMI Al-Amien Boarding School and Annuqayyah Mantiqah Latee Guluk-Guluk Sumenep Madura, also to know the running of Arabic cultural activities in both institutes.The form of this research is Qualitative Research which is used descriptive approach. While, data collecting technique uses interview with several informer which is consisting of Responsibiliters, Supervisors, and Arabic Teachers. And also, direct observation to the field and utilizing several document which is regarded with this research.Based on the result of the research shows that: First; there are differences between the implementation of Arabic Learning Method for Development of Speaking Skill at both institutes. Besides, in language achievement side both are increasing and competitive. In language center of TMI Al-Amien Boarding School has been using four methods, and they are: Direct Method, Repeat Method, Conversation Method, and Expressing Method. And also, in DALFIS has been using two methods, they are: Grammar Method and Translation Method.Exactly between Markazul Lughah in TMI Al-Amien Prenduan Boarding School and DALFIS Annuqayah Mantiqah Latee Guluk-Guluk have many differences according to surpluses and decreases.